Why Entrepreneurs Choose Risky R&D Projects - but still not risky enough - Erika Färnstrand Damsgaard; Per Hjertstrand; Pehr-Johan Norbäck; Lars Persson; Helder Vasconcelos (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines how entrepreneurs and incumbents differ in R&D strategies. We show that entrepreneurs have incentives to choose projects with higher risk and a higher potential in order to reduce expected commercialization costs. However, entrepreneurs may still select too safe projects from a social point of view, since they do not internalize the business stealing effect. Commercialization support induces entrepreneurship but may lead to mediocre entrepreneurship by inducing entrepreneurs to choose less risky projects, whereas R&D support encourages entrepreneurship without affecting the type of entrepreneurship. We develop a regression framework to test empirical predictions of the model. Within our regression framework we derive and attach statistical decision hypotheses corresponding to each prediction. Using a unique data set of Swedish patents and innovators, we find strong empirical support for these predictions.
Keywords: K23; 330; entrepreneurship; R&D; entry deterrence